Studio Jubileumi : 1958-1978 : Festmény - Szobor - Grafika - Box - Platz. - Magyar Nemzeti Galéria, Budapest (Budapest : Magyar Nemzeti Galéria, 1978)
Aknay, Janos ; Babos, Laszlo ; Barabas, Marton ; Birkas, Istvan ; Bodoczky, Istvan ; Budai Tibor ; Buhaly, Jozsef ; Dienes, Gabor ; Duschanek, Janos ; Eisenmayer, Tibor ; Farsangh, Sandor ; Fabian, Gyongyver ; Fabian, Pal ; etc.
Studio Jubileumi : 1958-1978 : Festmény - Szobor - Grafika - Box - Platz, Magyar Nemzeti Galéria, Budapest, December 1978
boek